A modified method for enzymatic isolation of and subsequent wax extraction from Arabidopsis thaliana leaf cuticle - Vráblová, Martina; Vrábl, Daniel; Sokolová, Barbora; Marková, Dominika; Hronková, Marie (Plant methods, 2020)
BACKGROUND: The plant cuticle represents one of the major adaptations of vascular plants to terrestrial life. Cuticular permeability and chemical composition differ among species. Arabidopsis thaliana is a widely used model for biochemical and molecular genetic studies in plants. However, attempts to isolate the intact cuticle from fresh leaves of Arabidopsis have failed so far. The goal of this study was to optimise an enzymatic method for cuticle isolation of species with a thin cuticle and to test it on several A. thaliana wild types and mutants. RESULTS: We developed a method for isolation of thin cuticles that allows reducing the isolation time, the separation of abaxial and adaxial cuticles, and avoids formation of wrinkles. Optical microscopy was used for studying cuticle intactness and scanning electron microscopy for visualisation of external and internal cuticle structures after isolation. Wax extracts were analysed by GC-MS. Isolation of intact cuticle was successful for all tested plants. The wax compositions (very-long-chained fatty acids, alcohols and alkanes) of intact leaves and isolated cuticles of wild type Col-0 were compared. CONCLUSIONS: We conclude that the optimised enzymatic method is suitable for the isolation of A. thaliana adaxial and abaxial cuticles. The isolated cuticles are suitable for microscopic observation. Analysis of wax composition revealed some discrepancies between isolated cuticles and intact leaves with a higher yield of wax in isolated cuticles.
Keywords: Enzymatic isolation; Wax; Fatty acids; Arabidopsis thaliana; Leaf cuticle